Ação relacional: ação como experiência de interação sob a perpectiva do agente implicado pelo sensível - Andrade, Maíra Leme de [UNESP] (2015)
This thesis consists of a research on the tools and dimensions that guide the creation and realization of relational action under the agent's perspective implied by the sensitive. From a conceptual point of view relational action is wide and variously discussed. However, in the practice of art making the links between the concepts and experiences presents specific issues that require towards practice, further research into action. At the crossroads between the fields of art and education this thesis presents a look at the relational action under the agent's perspective, in the sense of the instruments of art making